Contested Common Land : Environmental Governance Past and Present. - Rodgers, Christopher P. (Earthscan, 2010)
This innovative and interdisciplinary book makes a major contribution to common pool resource studies. It offers a new perspective on the sustainable governance of common resources, grounded in contemporary and archival research on the common lands of England and Wales - an important common resource with multiple, and often conflicting, uses. It encompasses ecologically sensitive environments and landscapes, is an important agricultural resource and provides public access to the countryside for recreation. Contested Common Land brings together historical and contemporary legal scholarship to e.